PENERAPAN GOOD TOURISM GOVERNANCE DI WISATA CAGAR BUDAYA ISTANA MAIMUN DALAM MEWUJUDKAN PARIWISATA BERKELANJUTAN OLEH DINAS PARIWISATA KOTA MEDAN - Angelina Esteria Riama; Erika Revida (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Maimun Palace is a tourist destination included in Medan's cultural heritage sites and holds significant potential for supporting sustainable tourism. Therefore, the implementation of Good Tourism Governance (GTG) is crucial for the management, development, and preservation of this tourist destination. This study aims to analyze the extent to which the principles of GTG are implemented by the Medan City Tourism Office, in collaboration with the Sultan Ma'moen Al Rasyid Foundation, in managing the Maimun Palace cultural heritage site to achieve sustainable tourism. This study uses a qualitative method with a descriptive approach. Data was collected through interviews with the Medan City Tourism Office, the Sultan Ma'moen Al Rasyid Foundation, business actors, tour guides, local communities, and tourists, as well as through observation and documentation. The data and information obtained were analyzed by researchers using Sunaryo's (2013) theory of Good Tourism Governance, which is relevant to the research problem. These ten principles include participation communities, stakeholders involvement, local ownership, resource sustainability, community aspirations, environmental carrying capacity, program monitoring & evaluation, environmental accountability, related community training, and publicity and advocacy of local cultural values are among these principles. Based on research conducted by researchers, the results show that the implementation of Good Tourism Governance at the Maimun Palace Cultural Heritage Site by the Medan City Tourism Office has been carried out, but not optimally. This can be seen from the limited community participation in economic aspects, weak coordination between stakeholders, and the need to improve the principles of environmental accountability and promotion of local culture. Therefore, there is a need to enhance cross-sector collaboration, community involvement in decision-making, and sustainable strategies covering economic, social, and environmental aspects. Implicitly, optimizing GTG principles is key to strengthening sustainable tourism governance in regional cultural heritage destinations.